2021
DOI: 10.1038/s41598-021-82848-3
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic view to wounding response in young Scots pine stems

Abstract: We studied the stress response of five-year-old Scots pine xylem to mechanical wounding using RNA sequencing. In general, we observed a bimodal response in pine xylem after wounding. Transcripts associated with water deficit stress, defence, and cell wall modification were induced at the earliest time point of three hours; at the same time, growth-related processes were down-regulated. A second temporal wave was triggered either at the middle and/or at the late time points (one and four days). Secondary metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…In the current study, transcriptomic analysis performed separately in the southern and northern populations of Scots pine revealed a significantly higher number of defense-related genes down-regulated under SHADE in both populations, supporting Scots pine's overall shade-intolerant nature (Ranade et al, 2019). Surprisingly, a higher number of defenserelated genes were found to be up-regulated in the northern population indicate that the pathways appear to be well conserved with the flowering plants with some variations (Kolosova & Bohlmann, 2012;Kovalchuk et al, 2015;Lim et al, 2021;Pascual et al, 2016). For example, conifers lack the FERULATE 5-HYDROXYLASE (F5H) gene, which is essential for the synthesis of S-type lignin, but the transformation with F5H was sufficient for the production of S-type lignin in the pine species Pinus radiata (Wagner et al, 2015).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the current study, transcriptomic analysis performed separately in the southern and northern populations of Scots pine revealed a significantly higher number of defense-related genes down-regulated under SHADE in both populations, supporting Scots pine's overall shade-intolerant nature (Ranade et al, 2019). Surprisingly, a higher number of defenserelated genes were found to be up-regulated in the northern population indicate that the pathways appear to be well conserved with the flowering plants with some variations (Kolosova & Bohlmann, 2012;Kovalchuk et al, 2015;Lim et al, 2021;Pascual et al, 2016). For example, conifers lack the FERULATE 5-HYDROXYLASE (F5H) gene, which is essential for the synthesis of S-type lignin, but the transformation with F5H was sufficient for the production of S-type lignin in the pine species Pinus radiata (Wagner et al, 2015).…”
Section: Discussionsupporting
confidence: 61%
“…With a few exceptions, the lignin pathway and defense response pathways are not as widely researched in conifers as they are in model systems such as Arabidopsis due to constraints in finding the mutants and creation of transgenic lines in conifers. However, a few studies conducted with reference to the lignin synthesis and defense response in conifers indicate that the pathways appear to be well conserved with the flowering plants with some variations (Kolosova & Bohlmann, 2012; Kovalchuk et al, 2015; Lim et al, 2021; Pascual et al, 2016). For example, conifers lack the FERULATE 5‐HYDROXYLASE (F5H) gene, which is essential for the synthesis of S‐type lignin, but the transformation with F5H was sufficient for the production of S‐type lignin in the pine species Pinus radiata (Wagner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in lesion area among families indicated that susceptibility to H. annosum varied among genotypes. Lesions observed in wounded control samples implied that defense responses could be triggered by mock inoculation (Lim et al, 2021 ). Moderate estimates of heritability for lesion area in FS and HS suggested that the lesion trait was influenced by host genetics.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq libraries were prepared, sequencing done, and data analysis performed as described in Lim et al (2016Lim et al ( , 2021. In short, all transcriptome libraries were mapped against Pinus EST collection version 9.0 (The Gene Index Databases, 2014) using SHRiMP alignment tool (David et al, 2011).…”
Section: Rna Sequencing Analysismentioning
confidence: 99%
“…We have previously studied the induction of stilbene biosynthesis under the developmental context of heartwood formation (Lim et al, 2016) and in response to mechanical wounding (Lim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%